PENGABDIAN KULIAH KERJA NYATA UNIVERSITAS RIAU KELURAHAN DAMON KECAMATAN BENGKALIS KABUPATEN BENGKALIS TAHUN 2023 - Ufira Isbah; Dzaky Ismu Raihan; Brillian Asyifa; Dinda Utami; Syifa Previa Pramodia; Tiara Adifa Fadillah; Nadya Moniqa; M. Sandi Arifin; M. Iftah Gian Alfarel; Said Muhammad Faruq (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2023)
With this UNRI 2023 KKN activity, we as the nation's successors are expected and required to apply the knowledge we have gained during lectures. Good, from science, technology, and art that is owned. We are expected to be motivators and facilitators of efforts to develop, especially rural areas. The community can share problems and solutions by discussing with KKN participants, so that cooperation is established in the local development process. The objectives that are expected to be achieved are the application and guidance to school children about disaster mitigation and bullying cases that are rampant in Indonesia.